Perancangan Aplikasi Opencart untuk Mendukung Pemasaran Digital Kerajinan Perabot UMKM Bukittinggi - Raihan Alfandi, M; Annas, Firdaus (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The furniture craft business in Bukittinggi plays an important role in improving the economy and preserving culture. However, problems in utilizing digital technology to market products cause limitations in reaching a wider market. To answer these challenges, this research aims to design an OpenCart-based application as a digital marketing solution in accordance with business needs in Bukittinggi. Research and development (R&D) methods are used in this research, which includes needs analysis, application design, and evaluation. MSME actors were interviewed to find out market characteristics and product types. The results of the research show that MSMEs in Bukittinggi can use OpenCart-based applications to market products, increase power competitiveness, and optimizing the marketing process. The OpenCart application is a good solution to help MSMEs in Bukittinggi market handicraft furniture products digitally. This application not only meets the needs of business actors in the digital era, but also helps increase the sustainability and competitiveness of MSMEs in local and national markets.